DO SHARIA MUTUAL FUNDS, SHARIA BONDS (SUKUK), AND SHARIA STOCKS AFFECT INDONESIA'S ECONOMIC GROWTH? - Khoirunisa, Nabilla; Amijaya, Rachmania Nurul Fitri; Santoso, Edy (Universitas Airlangga, 2025)
The growth of investment instruments is not always in line with national economic growth. This phenomenon raises questions about how much real influence Islamic capital market instruments have on Indonesia's economic growth. This study aims to examine the influence of sharia mutual funds, sharia bonds (sukuk), and sharia stock on Indonesia's economic growth from 2011-2024. This study uses a quantitative approach with Ordinary Least Squares (OLS) methods, multiple linear regression. The data used is quarterly time series data, with the sharia mutual fund indicator represented by the Net Asset Value (NAB), sukuk by the total issuance of corporate sukuk, and sharia stocks by the market capitalization of the Jakarta Islamic Index (JII). The results of the study show that, partially, sharia mutual funds and sharia stocks have a positive and significant effect on economic growth. However, Islamic bonds (sukuk) do not have a significant impact on economic growth. Keywords: Sharia Mutual Funds, Sharia Bonds, Sukuk, Sharia Stocks, Economic Growth